Comparison of Bone Conduction of Hearing in Patients with Benign and Malignant Types of Chronic Suppurative Otitis Media - M. Andre Darmawan; Ni Kadek Mega Suryantini (Experimental Student Experiences, 2024)
One of the main problems associated with hearing loss is chronic suppurative otitis media (CSOM). The purpose of this study was to determine the comparison of conduction of the auditory ossicles in patients with benign type chronic suppurative otitis media and malignant type otitis. Chronic suppurative media (CSOM) is a chronic infection of the mucosa and periosteum of the middle ear which is characterized by continuous discharge of fluid from the ear canal and perforation of the tympanic membrane. CSOM is divided into two types, namely the safe type or what is called benign and the dangerous or malignant type. Patients suffering from CSOM can experience conductive hearing loss which has a fairly high incidence rate. Chronic suppurative otitis media is one of the most common diseases in the world, especially in developing countries, which if not treated quickly can lead to seriousness. So the researchers wanted to examine the comparison of hearing bone conduction in patients with benign and malignant type of chronic suppurative otitis media. In addition, there are significant differences in the distribution of types of hearing loss between benign and malignant types of Chronic Suppurative Otitis Media (CSOM) patients. The benign type of CSOM is dominated by conductive deafness, while the malignant type of CSOM tends to have conductive and mixed deafness.